The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1128/jvi.02242-09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Disulfide-Stabilized Structure on the Specificity of Helper T-Cell and Antibody Responses to HIV Envelope Glycoprotein gp120

Abstract: CD4؉ helper T cells specific for human immunodeficiency virus type 1 (HIV-1) are associated with control of viremia. Nevertheless, vaccines have had limited effectiveness thus far, in part because sequence variability and other structural features of the HIV envelope glycoprotein deflect the immune response. Previous studies indicated that CD4؉ T-cell epitope dominance is controlled by antigen three-dimensional structure through its influence on antigen processing and presentation. In this work, three disulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…In humans, HLA variation is expected to influence the identity of immunodominant and immunoprevalent antigens in specific individuals. Model systems have identified additional factors controlling epitope choice for CD4 T cells, including naïve T-cell repertoire (5), antigen abundance (6), antigen folding (7), protease processing and epitopeflanking regions (8), and antigenic competition (9).…”
mentioning
confidence: 99%
“…In humans, HLA variation is expected to influence the identity of immunodominant and immunoprevalent antigens in specific individuals. Model systems have identified additional factors controlling epitope choice for CD4 T cells, including naïve T-cell repertoire (5), antigen abundance (6), antigen folding (7), protease processing and epitopeflanking regions (8), and antigenic competition (9).…”
mentioning
confidence: 99%
“…These results indicate that disulfide bonds can limit T-cell responses, but it remains unclear whether disulfide bonds influence T-cell responses in individuals that have normal GILT function. Following immunization of BALB/c mice, we noted a distinct absence of T-cell responses from regions of HIV gp120 that are enriched in disulfide bonds, but elimination of individual disulfide bonds caused broad reductions in the T-cell response, rather than local increases (30). We attributed the reductions to proteolytic destruction of the antigen, which reduced the amount of antigen fragments available for presentation.…”
Section: T He Specificity and Phenotype Of Cd4mentioning
confidence: 87%
“…Elimination of the 298-to-331 or 385-to-441 disulfides caused severe defects in folding, assembly, or export of the proteins, whereas elimination of the 378-to-441 disulfide had no consequence for expression or function. We found that elimination of any one of these three disulfides affected the conformation of gp120 and reduced the T-cell responses in BALB/c mice (30). Deletion of the 298-to-331 and 385-to-414 disulfides caused severe and moderate destabilization of gp120, respectively, resulting in globally reduced T-cell responses.…”
Section: T He Specificity and Phenotype Of Cd4mentioning
confidence: 93%
See 1 more Smart Citation
“…It has been documented [19] that the Fc fragment does not bind to Ags but acts as initiation of the complement cascade, a process that leads to the lysis of the target cells or mediates phagocytosis [20][21].…”
Section: Discussionmentioning
confidence: 99%